The Pathophysiology of Heart Failure: A Review Article: Patofisiologi Gagal Jantung: Sebuah Artikel Ulasan - Hussein, Wathiq Faraon (Universitas Muhammadiyah Sidoarjo, 2024)
Heart failure (HF) continues to be a major issue in the US and around the world, leading to high rates of morbidity and death at a significant financial burden on healthcare. A basic comprehension of the processes that underlie the heart failure (HF) adaptive response has resulted in the identification of multiple channels of compensation, which have been the focus of medical and pharmacological treatments intended to lessen the debilitating condition. To increase HF patients' chances of survival, further research is required to find novel targets. Highlights: Heart failure causes high morbidity, mortality, and financial burden. Understanding HF mechanisms aids medical and pharmacological interventions. Further research needed for novel treatment targets and improved survival. Keywords: Pathophysiology, Heart Failure, Review